Redirection of CAR-T Cell Cytotoxicity Using Metabolic Glycan Labeling with Unnatural Sugars - Cha, Jeong Hyeon; Kim, Eunsu; Lee, Hyeong Ji; Lee, Young Ho; Lee, Jeonghyun; Kim, Eunha; Kim, Chan Hyuk (Journal of Medicinal Chemistry, 2023)
T cells expressing chimeric antigen receptors (CAR-T cells) have shown unprecedented clinical responses against hematological malignancies. However, some patients relapse after CAR-T cell therapy due to antigen-negative escape variants. Additionally, CAR-T cell therapies showed limited clinical efficacy in solid tumors with high antigen heterogeneity. To overcome this, we metabolically labeled the glycans on cancer cells to redirect CAR-T cell cytotoxicity regardless of the endogenous antigen expression status of the cancer cells. We found that modifying cancer cells with N-azidoacetylmannosamine and bicyclo[6.1.0]non-4-yne-fluorescein isothiocyanate can elicit selective and durable cytotoxicity of anti-FITC CAR-T cells. Furthermore, we demonstrated that dinitrophenyl-conjugated sialic acid (Sia-DNP) generated DNP-modified glycans on cancer cells in situ that could be effectively targeted by anti-DNP CAR-T cells to eradicate established tumors in xenograft models. Our study illustrates that metabolic glycan labeling using unnatural sugars can be combined with CAR-T cell therapy to provide novel cancer immunotherapy for solid tumors that lack viable target antigens.
Keywords: Humans; Immunotherapy; Immunotherapy, Adoptive; Neoplasm Recurrence, Local; Receptors, Antigen, T-Cell; Receptors, Chimeric Antigen; T-Lymphocytes; Xenograft Model Antitumor Assays